The reciprocal relationship between nonverbal behavior and sports performance in a cross-lagged panel model - Bünemann, Stephanie; Schweizer, Geoffrey (Psychology of sport and exercise, 2021)
Objectives - The aim of the present research is to investigate the relationship between nonverbal behavior (NVB) and sports performance in a longitudinal design using cross-lagged panel models (CLPMs). - Method - In our study NVB and performance were measured at eight time points (n1) in 48 basketball matches (n2), resulting in N = 384 data points. Cross-lagged paths between NVB and performance were analyzed in multilevel models, with NVB at time point t-1 predicting performance at time point t and performance at time point t-1 predicting NVB at time point t. Performance was measured as the score difference between one team to the opposing team within a time point. NVB was rated on a scale from dominance to submissiveness by two blinded raters. Dependence of performance measures between time points was eliminated by two different approaches, resulting in two different measurements of performance. - Results - Results indicate an effect of NVB at time point t-1 on performance at time point t for one of the methods of performance. Contrary to our hypothesis and evidence from previous findings, there was no effect of performance at time point t-1 on NVB at time point t for neither method of measuring performance. - Conclusions - This study supports a positive relationship between NVB and sports performance, more so in the direction of NVB predicting performance.
Available online 5 May 2021
Gesehen am 14.07.2021